2006
DOI: 10.1111/j.1365-2915.2006.00625.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution pattern of oviposition in the mosquito Aedes aegypti in relation to urbanization in Buenos Aires: southern fringe bionomics of an introduced vector

Abstract: The distribution of Aedes aegypti (L) (Diptera: Culicidae) oviposition in Buenos Aires City is spatially heterogeneous. Oviposition activity was monitored for a year with a grid of 279 traps at 850-m intervals that were serviced weekly. Geostatistics were used for the spatial analysis and generalized linear regression to model oviposition as a function of demographic and environmental variables. The proportion of weeks infested and the total number of eggs showed spatial continuity and were higher in areas tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
89
0
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(97 citation statements)
references
References 32 publications
(39 reference statements)
2
89
0
6
Order By: Relevance
“…La transmisión de la enfermedad es multicausal, y en ella intervienen diferentes factores entomológicos, socioeconómicos y climáticos (3,4). En particular, se ha evidenciado que estos últimos juegan un papel importante en la distribución espacial y temporal de la enfermedad (5,6).…”
Section: Resultsunclassified
“…La transmisión de la enfermedad es multicausal, y en ella intervienen diferentes factores entomológicos, socioeconómicos y climáticos (3,4). En particular, se ha evidenciado que estos últimos juegan un papel importante en la distribución espacial y temporal de la enfermedad (5,6).…”
Section: Resultsunclassified
“…Our findings are in accordance with the oviposition pattern of Ae. aegypti in Buenos Aires City described by Carbajo et al (2006); lower infestation levels were found in areas with higher human populations or higher densities of flats.…”
Section: Discussionmentioning
confidence: 99%
“…Within the Federal District, the spatial pattern of Ae. aegypti oviposition was associated with an urbanisation gradient (Carbajo et al 2006) and the presence of immatures at the microhabitat scale was related to shaded and vegetated surroundings (Vezzani et al 2005). However, these studies were restricted to highly urbanised areas and the knowledge of both mosquito vectors in small towns, as well as in used tires, is truly limited in the region.…”
mentioning
confidence: 99%
“…Sampling points were located more than 4 km apart, a distance much larger than the flight range of the species, but within residential neighbourhoods that had low human densities and consisted mostly of houses with gardens and backyards. In Buenos Aires (the capital city of Argentina), Carbajo et al (2006) found that oviposition activity was higher in areas with a larger proportion of houses and lower human density, compared to more urbanized areas with high-rise buildings and higher human density. A positive association was also found between oviposition and industrial sites, possibly due to a high density of water containers.…”
Section: Discussionmentioning
confidence: 99%